Analysis of Digital Operation of Rural Sewage Treatment System in Big Data Environment by Discrete Dynamic Modeling Technology - Lixuan, Wang (Frontiers in Energy Research, 2022)
Sewage treatment is a process with high energy consumption and pollution. In the current situation of energy shortage and fierce competition in the paper industry market, how to reduce the energy cost is related to the survival and development of every sewage treatment plant. With the rise of big data environment in the internet, discrete dynamic modeling technology has developed very rapidly. Discrete dynamic modeling technology is a dynamic model system that can connect the information of different things, so as to form a dynamic model system that can control all devices or data. The object attributes processed by the model system also determine the nature of the dynamic model system. As we all know, the big data environment is a large database with complex data types, so the dynamic model system in the big data environment is nonlinear. This paper mainly studies the historical development trend of big data environment and discrete dynamic modeling technology, as well as the stability method of five level H-bridge when discrete dynamic modeling technology controls rural sewage treatment system. Finally, the control of chaotic bifurcation in discrete dynamic model system under digital background is studied. It includes the rectifier modeling of the current data required by large devices in the sewage treatment system and the result analysis of the generated values.